2008
DOI: 10.1128/jcm.00628-08
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Human Enterovirus 71 in the United Kingdom from 1998 to 2006

Abstract: The last decade witnessed a significant increase in epidemic activity of human enterovirus 71 (EV71) in the Western Pacific Region (WPR). In most European countries, this risk is unrecognized despite occasional cases of severe disease and two severe outbreaks in Eastern Europe 30 years ago. In this study we report the first examination of the molecular epidemiology of EV71 in the United Kingdom from 1998 to 2006. Genomic regions encoding the 1D coat protein (VP1) and 3D polymerase (Pol) from 32 EV71 isolates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 27 publications
6
97
0
Order By: Relevance
“…In contrast to the epidemiological features observed for genogroup C viruses in the West Pacific region, the circulation of these viruses in Europe was not associated with epidemics over the last 30 years. The EV-71 infections in the patients from Austria, France and Germany were sporadic, mainly associated with mild illnesses including HFMD, and were similar to those described earlier in the UK, the Netherlands and Hungary (Bible et al, 2008;van der Sanden et al, 2009;Kapusinszky et al, 2010). However, among the patients included in our study, a syndrome of fatal acute respiratory distress was reported in an infant with an EV-71 C1 infection and in a young child with a C2 virus infection (Vallet et al, 2009 This observation explains the differences between the proportions of the C1 and C2 strains in our study (49.4 % and 42.4 %, respectively) and those (78 % and 12 %) reported in an earlier study (Bible et al, 2008), which included viruses collected during the period 1998-2006.…”
Section: Consistent Phylogenies Of Circulating Ev-71 Strains Obtainedsupporting
confidence: 56%
See 2 more Smart Citations
“…In contrast to the epidemiological features observed for genogroup C viruses in the West Pacific region, the circulation of these viruses in Europe was not associated with epidemics over the last 30 years. The EV-71 infections in the patients from Austria, France and Germany were sporadic, mainly associated with mild illnesses including HFMD, and were similar to those described earlier in the UK, the Netherlands and Hungary (Bible et al, 2008;van der Sanden et al, 2009;Kapusinszky et al, 2010). However, among the patients included in our study, a syndrome of fatal acute respiratory distress was reported in an infant with an EV-71 C1 infection and in a young child with a C2 virus infection (Vallet et al, 2009 This observation explains the differences between the proportions of the C1 and C2 strains in our study (49.4 % and 42.4 %, respectively) and those (78 % and 12 %) reported in an earlier study (Bible et al, 2008), which included viruses collected during the period 1998-2006.…”
Section: Consistent Phylogenies Of Circulating Ev-71 Strains Obtainedsupporting
confidence: 56%
“…A sequence reported earlier (GenBank accession no. AF119795) comprising a known recombination event (Bible et al, 2008) was used as a positive control. The RDP analysis indicated statistical evidence for the presence of recombination breakpoints in only one 1D sequence which was subsequently excluded.…”
Section: Enterovirus 71 Evolutionary Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in our model the infected individuals are divided into two subgroups (symptomatic and asymptomatic). Moreover, enteroviruses have a strong infectivity, the pathogens being capable of surviving for long periods in suitable conditions outside the host (Chung et al, 2001;Bible et al, 2008;Han et al, 2010). So contaminated environments are also important sources from which it is possible for susceptible to become infected.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptible infants are usually infected by close contact with infected individuals. Note that the pathogen of EV71 can survive for a long period outside the host in suitable conditions (Chung et al, 2001;Bible et al, 2008;Han et al, 2010) and even 75% alcohol can not eliminate the virus. HFMD patients and asymptomatic recessive individuals, releasing virus to the environment, are the major infectious sources but there is also some evidence that susceptible individuals can be infected via touching free-living pathogens in the environment.…”
Section: Introductionmentioning
confidence: 99%